Enzymatic and toxinological activities of Hypnale hypnale (hump-nosed pit viper) venom and its fractionation by ion exchange high performance liquid chromatography - Tan,CH (2011)
Hypnale hypnale (hump-nosed pit viper) has been recently identified as one of the medically important venomous snakes in Sri Lanka and on the southwestern coast of India. The characterization of its venom is essential for understanding the pathophysiology of envenomation and for optimizing its management. In the present study, the biological properties of Hypnale hypnale venom and venom fractions obtained using Resource Q ion exchange chromatography were determined. The venom exhibited toxic activities typical of pit viper venom, comparable to that of its sister taxon, the Malayan pit viper (Calloselasma rhodostoma). Particularly noteworthy were its high activities of thrombin-like enzyme, proteases, phospholipase A2, L-amino acid oxidase and hyaluronidase. The thrombin-like enzyme was mainly acidic and distributed over several chromatography fractions, indicating its existence in multiple isoforms. The hemorrhagic and necrotic activities of the venom were likely associated with the proteolytic enzyme found mainly in the basic fraction. Phospholipase A2 and phosphomonoesterase exist in both acidic and basic isoforms, while L-amino acid oxidase and hyaluronidase are highly acidic. The venom clotting activity on fibrinogens showed distinct species specificity in the following increasing order for clotting time: bovine < rabbit < goat < human < horse < < dog, and was comparable to that of C. rhodostoma venom. Its clot formation on human fibrinogen is gradual and prolonged, a phenomenon suggestive of consumptive coagulopathy as a complication observed clinically. At an intramuscular sublethal dose, the venom did not cause acute kidney injury in a rodent model, contrary to the positive control group treated with Daboia russelii venom. Nephrotoxicity may result from higher venom doses in the context of coagulopathy, as a complication provoked by venom hematoxicity.